A Short Enantioselective Synthesis of (S)-Levetiracetam through Direct Palladium-Catalyzed Asymmetric N-Allylation of Methyl 4-Aminobutyrate - Albat, Dominik; Neudörfl, Jörg-Martin; Schmalz, Hans-Günther (Synlett, 2021)
An exceedingly short and enantioselective synthesis of the antiepileptic drug (S)-levetiracetam was elaborated. As the chirogenic key step, a Pd-catalyzed asymmetric N-allylation of methyl 4-aminobutyrate was achieved in the presence of only 1 mol% of a catalyst prepared in situ from [Pd(allyl)Cl]2 and a tartaric acid-derived C2-symmetric diphosphine ligand.
Keywords: asymmetric catalysis; palladium catalysis; chiral ligands; amino acid derivatives; ozonolysis; levetiracetam